THE PROBLEMS OF TEACHING ENGLISH IN ASSAMESE MEDIUM SECONDARY SCHOOLS OF ASSAM - Dr. Darsana Changkakoti (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
English occupies the place of international link language and thus is regarded as an important subject of study in the secondary schools. However the teacher is faced with a number of challenges when it comes to teaching of English in the vernacular schools. Thus an attempt has been made in this study to know about the problems faced by the English language teachers in teaching English to the secondary school students of Assam with special emphasis on the Assamese medium secondary schools of Assam. Self constructed interview schedule was used to collect the necessary data and simple percentage and graphical representation was used to analyze the data quantitatively. A sample of 30 teachers from 10 schools were selected purposefully for the present study. It was found that most of teachers neglect the use of teaching aids in their teaching of English. They also lack necessary training in teaching English and hence are faced with numerous difficulties.